1992
DOI: 10.1164/ajrccm/146.4.855
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Lung Function Decline in Subjects with Respiratory Symptoms

Abstract: The relation of respiratory symptoms and lung function has not been extensively investigated. To determine better the rate of FEV1 decline in subjects reporting persistent wheeze, chronic cough, chronic phlegm, and/or dyspnea, longitudinal data from an adult population sample of 3,948 subjects (1,757 men; 2,191 women) followed for 12 yr were analyzed. At the initial and subsequent follow-up visits, subjects completed a standardized respiratory questionnaire and performed spirometry using the same methods and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
80
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(89 citation statements)
references
References 5 publications
7
80
2
Order By: Relevance
“…Thirty-®ve percent were current smokers, 35% former smokers and 30% non-smokers, similar to those of our study group (33%, 38% and 29%, respectively). By comparison of current ®ndings with those obtained by Sherman et al 20 it is apparent that complaints of breathlessness, or any symptom, in subjects with tetraplegia or paraplegia in all smoking categories far exceeded those observed in the general population (Table 4). In addition, among subjects with tetraplegia, wheeze was more prevalent among current and former smokers and all symptoms were more prevalent among non-smokers.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Thirty-®ve percent were current smokers, 35% former smokers and 30% non-smokers, similar to those of our study group (33%, 38% and 29%, respectively). By comparison of current ®ndings with those obtained by Sherman et al 20 it is apparent that complaints of breathlessness, or any symptom, in subjects with tetraplegia or paraplegia in all smoking categories far exceeded those observed in the general population (Table 4). In addition, among subjects with tetraplegia, wheeze was more prevalent among current and former smokers and all symptoms were more prevalent among non-smokers.…”
Section: Discussionmentioning
confidence: 52%
“…Among ablebodied men, the reporting of any respiratory symptom was associated with a reduction in initial lung function and more rapid decline in height-adjusted forced expiratory volume in one second (FEV1). 20 In addition, after adjustment for height, age and cigarette smoking, healthy men with cough or phlegm demonstrated accelerated loss in FEV1. In a study of the natural history of chronic air¯ow obstruction, symptoms of cough and phlegm, wheeze, and breath- Figure 4 (A) Prevalence of cough combined with phlegm among positive responders for increasing episodes or occurring greater than three weeks per year.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The onset of cough and phlegm was associated with a significant decline in FEV 1 /FVC. An early study by Fletcher and coworkers in able-bodied individuals found that chronic cough and phlegm were not associated with lung function decline (43), whereas more recent studies have reported significant associations (44,45). Persons in the lowest MIP quartile had a greater decline in FVC and FEV 1 and also had the greatest decline in MIP across each test interval.…”
Section: Discussionmentioning
confidence: 98%